The role of arts and cultural education in the context of sustainable development: concluding remarks - Luísa Veloso; Wagner E.; Pachova N.; Suominen A.; Nielsen, C. (Arts. sustainability and education. – ENO Yearbook 2, 2021)
This chapter aims to reflect on how the relation between arts or cultural education and sustainable development, specifically the Sustainable Development Goals [SDGs] (United Nations. 2015. Transforming our world: the 2030 Agenda for Sustainable Development. https://www.refworld.org/docid/57b6e3e44.html.), is addressed in this book, drawing conclusions and directions for future research and for the work of the European Network of Observatories in the Field of Arts and Cultural Education (ENO).